Door-to-Door Culture of Commuters: Its Impact on the Road Carrying Capacity - -Lutap, Rivera; A, Jocelyn; Orlean G. , Dela Cruz (International Journal of Sustainable Construction Engineering and Technology, 2023)
Barriers to exchange of goods and ideas have shrunk because of technology. Mobility is one of the greatest contributions of industrialization and urbanization. This has also changed the lifestyle of millions of people. The vision of seamless travel has been a byword in regional and urban planning. Providing intermodal facilities has become the top priority of the private and public sector. The concept of door to door, from home to work to places of recreation and other social activities should provide accurate, safe and comfortable travel for commuters. This concept is directed in long distance travel. However, the concept of door to door journey for commuters in the City of Manila specifically in the District of Sta. Mesa took a different epithet. The Polytechnic University of the Philippines was used as a model on how people would literally go out of a building and hop on a tricycle to go to another destination even when the distance is less than a kilometer. The paper investigates on the choices of the commuters specifically of the students, faculty, and staff of this university. It looks into how this phenomenon affects the carrying capacity of the road and explores complimentary and supplementary existence of this transport phenomena of door to door culture of the pedestrian in this case, the PUP community and the constituents of the District of Sta. Mesa, Manila.